2020
DOI: 10.32861/jbr.65.34.40
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Chickpea Varieties (Cicer arietinum L.) at Bule Hora and Abaya Southern Ethiopia

Abstract: Chickpea is among the major pulse crops grown in southern Ethiopia including Borana and West guji zone. The area has potential to the production of Chickpea for food and nutrition security as well as export commodity. However, scarcity of varieties that fit to the environment is one of the major constraints of production. Therefore, this experiment was conducted to evaluate 9 chickpea varieties to select adaptable varieties for yield and agronomic traits. The field experiment was conducted in 2017 and 2018 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The highest plant height was observed from genotypes KWR-108 (47cm) while the lowest plant height was observed from genotypes Tara (38 cm). Similar results for mean and range for plant height in Chickpea varieties were also reported previously by (Dan et al, 2016, Ejara et. al., 2020and Ercan et.…”
Section: Growth Traitssupporting
confidence: 90%
See 1 more Smart Citation
“…The highest plant height was observed from genotypes KWR-108 (47cm) while the lowest plant height was observed from genotypes Tara (38 cm). Similar results for mean and range for plant height in Chickpea varieties were also reported previously by (Dan et al, 2016, Ejara et. al., 2020and Ercan et.…”
Section: Growth Traitssupporting
confidence: 90%
“…Likewise, the seed yield of the chickpea genotypes ranges from 0.6 to 2.8, 1.5 to 6.9, and 1.2 to 4.4 (ton/ha) respectively during two growing seasons and overall pooled mean. Further, (Dan, et al 2016, Ejara et. al.…”
Section: Yield and Yield Componentsmentioning
confidence: 99%
“…Flowerin took the minimum number of days to 90% physiological maturity among the Kabuli type chickp ea varieties at Debre Zeit station (Table 7). Ejigu Ejara et al (2020) reported that the earliest mat uring varieties were Dimtu (99.75 days), followed by Dalota (101.29 days), while the late maturing variety was Dhera (113.37days), and followed by Hora (110.58days) suggested nearly similar findings.…”
Section: Days To 50%flowering and 90% Physiological Maturity (Df Dpm)mentioning
confidence: 70%